A unicenter, prospective study of Guillain‐Barré syndrome in Spain. (10th April 2019) - Sedano, María J.; Orizaola, Pedro; Gallardo, Elena; García, Antonio; Pelayo‐Negro, Ana L.; Sánchez‐Juan, Pascual; Infante, Jon; Berciano, José
Abstract : Objective: We report a prospective study analysing clinical characteristics, subtyping and prognosis in Guillain‐Barré syndrome (GBS). Method: The study was based on consecutive GBS patients admitted between 2009 and 2017. Disability was serially assessed using the GBS disability scale. Results: Fifty‐six GBS patients were identified with an average age of 55 years (range, 5‐86 years) and a male/female ratio of 2.1. The interval to nadir was <7 days in 59% of cases, and 7 to 28 days in the remainder; at nadir, 35.5% of patients were able to walk unaided, and 64.5% did not. Mechanical ventilation was needed in 20% of cases. There were two fatal cases. Clinical variants included paraparetic GBS seven cases, Miller Fisher syndrome one case, and acute sensory ataxic neuropathy (ASAN) one case. Serial electrophysiology showed a demyelinating pattern in 62.5% of cases, axonal in 28.5%, inexcitable in 1.8%, equivocal in 1.8%, and normal in 5.4%. Very early (1 to 4 days after onset) electrophysiology was done in 18 patients; equivocal or normal features in six of them evolved into an axonal pattern in four. Reversible conduction failure of sensitive nerves occurred in ASAN. Antiganglioside antibodies were only detected in axonal GBS. At 24‐month follow‐up, functional outcome did not differ between demyelinating and axonal GBS. Clinico‐pathological correlation in an early fatal case is reported. Conclusions: This GBS study demonstrates comparable clinical features to previous investigations from well‐defined populations. There was a relatively high prevalence of axonal GBS. We provide new pathophysiological insights on nerve conduction alterations.